Confidence in indirect assessment of foot-and-mouth disease vaccine potency and vaccine matching carried out by liquid phase ELISA and virus neutralization tests - Robiolo, Blanca (2010)
The necessity of avoiding the use of animals in vaccine potency testing has been widely recognized. The repeatability and reproducibility of the Expected Percentage of Protection (EPP) as a serological potency surrogate for A24 Cruzeiro foot-and-mouth disease virus (FMDV) strain was assessed, and compared with the results obtained with challenge in the Protection against Podal Generalization (PPG) test. To determine the EPPs, the serum titers obtained by liquid phase blocking competitive ELISA (lpELISA) and virus neutralization (VNT) in 10 potency trials using the same A24 Cruzeiro vaccine, were interpolated into previously validated logit transformation curves that correlate PPG with serology. Indirect serological assessment of vaccine matching between the serotype A FMDV strains A24 Cruzeiro and A/Argentina/01 was also carried out by lpELISA and VNT. The results obtained in this study strongly support the replacement of challenge tests for vaccine potency by indirect serological assays, at least for A24 Cruzeiro FMDV strain. While determination of EPPs by lpELISA titers showed an excellent repeatability, reproducibility and concordance with PPG for vaccine potency, assessments of cross-protection by VNT titers were more consistent with the PPG outcome.